2011
DOI: 10.1186/1477-7827-9-146
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D - roles in women's reproductive health?

Abstract: In the past few years a growing interest in vitamin D can be observed in the lay and biomedical literature due to findings demonstrating a low vitamin D status in the population. In addition to its importance for the regulation of calcium and phosphorus homeostasis recent epidemiologic studies have observed relationships between low vitamin D levels and multiple disease states. This secosteroid hormone also regulates the expression of a large number of genes in reproductive tissues implicating a role for vitam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0
18

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 173 publications
1
73
0
18
Order By: Relevance
“…Vitamin D regulates the expression of numerous genes, including genes associated with steroidogenesis of sex hormones in female reproductive tissues, which also extends to estradiol and progesterone (26,27). Previous studies on humans and animals demonstrated that low vitamin D levels are associated with reduced fertility, poor in vitro fertilization outcome, and polycystic ovary syndrome (27,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D regulates the expression of numerous genes, including genes associated with steroidogenesis of sex hormones in female reproductive tissues, which also extends to estradiol and progesterone (26,27). Previous studies on humans and animals demonstrated that low vitamin D levels are associated with reduced fertility, poor in vitro fertilization outcome, and polycystic ovary syndrome (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on humans and animals demonstrated that low vitamin D levels are associated with reduced fertility, poor in vitro fertilization outcome, and polycystic ovary syndrome (27,28). In addition, the predicted plasma 25 (OH) D 3 levels have been observed to be inversely associated with endometriosis (27,11). The role of vitamin D in the development and progression of endometriosis has also been extensively investigated in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Human and animal data suggests that low vitamin D status is associated with impaired infertility, endometriosis, and polycystic ovary syndrome. 13 Recent data on vitamin D provides new insights in the complex pathogenesis and treatment of infertility. Several animal and human studies suggests that vitamin D is involved in many functions of the reproductive system in both genders.…”
Section: Synthesis Of Vitamin Dmentioning
confidence: 99%
“…Besides the well-known function of vitamin D in promoting in vitro bone mineralization and prevention of osteoporosis and bone fracture through intestinal calcium absorption [3,4], mounting evidence has linked hypovitaminosis D to musculoskeletal diseases [5], cancer [6], autoimmune diseases, type 2 diabetes, cardiovascular disease [6,7] and all-cause mortality [5]. The main source of vitamin D is cholecalciferol (vitamin D3), synthesized in the skin by ultraviolet radiation [2]; pro-vitamin D3 (7-dehydrocholesterol) is converted to pre-vitamin D3, which isomerizes into cholecalciferol and is later converted to calcitriol (1,25(OH) 2 D 3 ) through a two-step enzymatic pathway involving liver 25-hydroxylase (CYP2R1) andkidney 1-α-hydroxylase (CYP27B1) [2,8,9]. Vitamin D status is assessed by measuring 25(OH)D 3 [8].…”
Section: Introductionmentioning
confidence: 99%
“…The main source of vitamin D is cholecalciferol (vitamin D3), synthesized in the skin by ultraviolet radiation [2]; pro-vitamin D3 (7-dehydrocholesterol) is converted to pre-vitamin D3, which isomerizes into cholecalciferol and is later converted to calcitriol (1,25(OH) 2 D 3 ) through a two-step enzymatic pathway involving liver 25-hydroxylase (CYP2R1) andkidney 1-α-hydroxylase (CYP27B1) [2,8,9]. Vitamin D status is assessed by measuring 25(OH)D 3 [8]. Currently, the Hormonal Studies [5,7].…”
Section: Introductionmentioning
confidence: 99%